2021
DOI: 10.1136/bmjpo-2021-001224
|View full text |Cite
|
Sign up to set email alerts
|

I-KID study protocol: evaluation of efficacy, outcomes and safety of a new infant haemodialysis and ultrafiltration machine in clinical use: a randomised clinical investigation using a cluster stepped-wedge design

Abstract: IntroductionThe I-KID study aims to determine the clinical efficacy, outcomes and safety of a novel non-CE-marked infant haemodialysis machine, the Newcastle Infant Dialysis Ultrafiltration System (NIDUS), compared with currently available therapy in the UK. NIDUS is specifically designed for renal replacement therapy in small babies between 0.8 and 8 kg.Methods and analysisThe clinical investigation is taking place in six UK centres. This is a randomised clinical investigation using a cluster stepped-wedge de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…First, the patient can be weighed before and after a dialysis treatment; we have reported that the NIDUS was very precise during 4-h clinical dialysis sessions in 6 kg babies, while a conventional Gambro AK200 pediatric dialyzer caused large fluid shifts that produced hypotension which needed urgent therapy [ 4 ]. A second approach is to weigh the dialysate, replacement and waste fluid bags before and after a dialysis session to determine the quantity of fluid added due to UF from the baby—this is the technique used in the IKID study [ 5 ]. The third, and simplest, approach is to do an in vitro study of the change in weight of a saline bag during ‘treatment’ as we have done here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the patient can be weighed before and after a dialysis treatment; we have reported that the NIDUS was very precise during 4-h clinical dialysis sessions in 6 kg babies, while a conventional Gambro AK200 pediatric dialyzer caused large fluid shifts that produced hypotension which needed urgent therapy [ 4 ]. A second approach is to weigh the dialysate, replacement and waste fluid bags before and after a dialysis session to determine the quantity of fluid added due to UF from the baby—this is the technique used in the IKID study [ 5 ]. The third, and simplest, approach is to do an in vitro study of the change in weight of a saline bag during ‘treatment’ as we have done here.…”
Section: Discussionmentioning
confidence: 99%
“…Currently in the UK, most babies weighing < 8 kg who undergo HT are treated off-license with continuous veno-venous hemofiltration (CVVH) using either the Prismaflex or the Aquarius devices, or the novel Newcastle infant hemodialysis and ultrafiltration system (NIDUS) for those in the IKID (Infant Kidney Dialysis and filtration) study. The IKID study is funded by the Efficiency and Mechanism Evaluation programme of the National Institute for Health Research, is designed to compare current practice including peritoneal dialysis with NIDUS [ 5 ] and has completed recruitment and will be reporting shortly. The NIDUS has been designed to treat babies of between 800 g and 8 kg and uses a volumetrically controlled syringe-driven circuit to regulate fluid balance, rather than using circuit pressures to regulate the UF control algorithms as occurs in conventional HT devices.…”
Section: Introductionmentioning
confidence: 99%
“…A dedicated neonatal or infant dialysis machine, CARPEDIEM, was introduced in clinical practice, while another machine, NIDUS, is currently under investigation. 28 , 29 , 30 , 31 However, only 15% of PICUs described availability of one of these dedicated neonatal or infant machines. Nonetheless, it should be highlighted that third- and fourth-generation machines have repeatedly been shown to have a high level of accuracy in children, and dedicated technology should be strongly recommended in children weighing less than 8 to 10 kg, especially because of smaller priming volumes and accurate ultrafiltration rates.…”
Section: Discussionmentioning
confidence: 99%
“…In case of insufficient desired toxin clearance, respondents preferred to change the CKRT modality, followed by increasing the effluent rate (eFigure 3B in Supplement 1). The CKRT dose was calculated mainly (72%) using a weight-based formula (mL/kg/h), and the median (IQR) CKRT dose among the PICUs was 35 (30-50) mL/kg/h in neonates and 30 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)…”
Section: Ckrt Initiation and Terminationmentioning
confidence: 99%
See 1 more Smart Citation